The Social Worlds of Nineteenth-Century Chamber Music : Composers, Consumers, Communities - Sumner Lott, Marie (Book collections on Project MUSE., 2015)
Marie Sumner Lott examines the music available to musical consumers in the 19th century, and what that music tells us about their tastes, priorities, and activities. Her social history of chamber music performance places the works of canonic composers such as Schubert, Brahms, and Dvorak in relation to lesser-known but influential peers.